2016
DOI: 10.1182/blood-2016-05-716662
|View full text |Cite
|
Sign up to set email alerts
|

Hospital volume and acute myeloid leukemia mortality in Medicare beneficiaries aged 65 years and older

Abstract: Acute myeloid leukemia (AML) is a fast-growing and lethal malignancy of the blood and bone marrow, with a 5-year mortality rate of 75%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…AKI patients' prognosis depends not only on the disease's etiology but also on the methods of diagnosis and management used in each medical setting [8]. Recent studies further proved that a larger hospital volume or case volume leads to better clinical outcomes in patients with various diseases, such as sepsis [9,10], leukemia [11], and those requiring surgery [12,13].…”
Section: Although Considerable Efforts Have Been Made To Tacklementioning
confidence: 99%
“…AKI patients' prognosis depends not only on the disease's etiology but also on the methods of diagnosis and management used in each medical setting [8]. Recent studies further proved that a larger hospital volume or case volume leads to better clinical outcomes in patients with various diseases, such as sepsis [9,10], leukemia [11], and those requiring surgery [12,13].…”
Section: Although Considerable Efforts Have Been Made To Tacklementioning
confidence: 99%
“…AML occurs mostly in elderly patients whose age is older when diagnosed, and their therapeutic efficacy and tolerance are significantly worse with age (3). In addition, there are often bleeding, infection or other adverse symptoms during the onset and treatment of the disease, which usually means worse prognosis (1). Therefore, the key to the diagnosis and treatment of AML is how to ensure the efficacy on AML patients while finding a safer treatment regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Its annual incidence is 3–4 patients per 100,000 people and its 5-year mortality is 75%. The incidence of its onset is increasing with age (13). Myeloid archaeocytes clonally proliferate in peripheral blood or bone marrow, which is the characteristic of AML (4).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous prior studies have shown the beneficial effect of a large HV on clinical outcomes in a wide variety of diseases or in patients needing operations or procedures. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 A larger HV is associated with larger caseloads and increased experience, and greater numbers of surgeons or physicians, both of which potentially lead to favorable outcomes for patients. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 Admissions to larger HV and DCV hospitals both were associated with lower in-hospital mortality, as expected, in a univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent attempts to clarify the association between hospital volume (HV) and in-hospital mortality showed that a larger HV is associated with increased survival in various diseases such as sepsis, breast cancer, chronic obstructive pulmonary disease, acute myeloid leukemia, peripheral arterial disease, and deep vein thrombosis, 7 , 8 , 9 , 10 , 11 , 12 , 13 as well as after surgical procedures. 14 , 15 HV is usually defined as the number of hospitalization cases 7 , 8 , 9 , 10 , 11 or specific procedures 12 , 13 , 14 , 15 at each hospital. Thus, a larger HV is associated with a greater number of case experiences, doctors with expertise in treating the disease, hospital infrastructure, and resources.…”
mentioning
confidence: 99%